Comparison of the effect of the rotation palatoplasty and V–Y pushback palatoplasty techniques on palate elongation with magnetic resonance imaging. Issue 6 (June 2015) - Isik, D.; Bora, A.; Yuce, S.; Davran, R.; Kocak, O.F.; Canbaz, Y.; Avcu, S.; Atik, B.
Abstract Most surgical techniques used in cleft palate repair require the extension of the palate to the pharynx. However, no adequate information exists regarding the extent to which this elongation obtained during operation continues in late postoperative period. In this study, we compared and measured palate elongation in patients with a cleft palate who underwent a V–Y pushback or rotation palatoplasty, by means of magnetic resonance images obtained before and 1 year after surgery. The hard palate, soft palate, and total palate lengths were measured for all of the patients, and the velopharyngeal opening area width was calculated. In patients who underwent the V–Y pushback technique (n = 13), the total palate and soft palate lengths were shortened by an average of 0.10 and 0.14 cm after surgery, respectively. However, the hard palate length was elongated by an average of 0.13 cm. In the rotation palatoplasty group (n = 13), the total palate, hard palate, and soft palate lengths were elongated by 0.57, 0.10, and 0.49 cm, respectively. The velopharyngeal opening was narrowed by 0.06 cm2 using the V–Y pushback technique and by 0.29 cm2 using the rotational palatoplasty. This study demonstrated that the palate does not elongate during the V–Y pushback technique, as expected. However, rotational palatoplasty elongates the soft palate.